2012
DOI: 10.1186/1472-6882-12-257
|View full text |Cite
|
Sign up to set email alerts
|

A water extract of Samchulkunbi-tang attenuates airway inflammation by inhibiting inos and MMP-9 activities in an ovalbumin-induced murine asthma model

Abstract: BackgroundIn this study, we investigated the effect of Samchulkunbi-tang water extract (SCTE) in an established mouse model of ovalbumin (OVA)-induced allergic asthma. The effects of SCTE on the production of Th1 and Th2 cytokines, eotaxin, and total and OVA-specific immunoglobulin E, inducible nitric oxide synthase expression, and matrix metalloproteinase-9 activity were measured.MethodsMice were sensitized on days 0 and 14 with an intraperitoneal injection of 20 μg ovalbumin (OVA) emulsified in 2 mg aluminum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…31 IL-4 promotes the differentiation and proliferation of Th2-type T cells, and the switching of B cells to produce IgG1 and IgE iso types antibodies. 37 In the present study, the serum level of Bt-specific IgG1 in Bt-sensitized mice was significantly reduced by administration of CA. The production of IL-4, from isolated splenocytes incubated in the presence of PWM, was remarkably inhibited by the addition of CA, and the modulation on IgG1 could be related the decrease in IL-4.…”
Section: Discussionsupporting
confidence: 52%
“…31 IL-4 promotes the differentiation and proliferation of Th2-type T cells, and the switching of B cells to produce IgG1 and IgE iso types antibodies. 37 In the present study, the serum level of Bt-specific IgG1 in Bt-sensitized mice was significantly reduced by administration of CA. The production of IL-4, from isolated splenocytes incubated in the presence of PWM, was remarkably inhibited by the addition of CA, and the modulation on IgG1 could be related the decrease in IL-4.…”
Section: Discussionsupporting
confidence: 52%
“…Our findings indicate that SSEW administration significantly decreased the increased Th2-type cytokines and chemokine production. Several studies have shown that modulation of Th1/Th2 cytokines can inhibit airway inflammation in OVA-induced mice [ 33 , 34 ]. Therefore, these findings suggest that SSEW attenuates airway inflammation through the modulation of the Th1/Th2 balance.…”
Section: Discussionmentioning
confidence: 99%
“…Samchulkunbi-tang (ST) is a traditional herbal medicine widely used for treatment of chronic gastritis, gastric ulcers and gastroptosis. It is a composite traditional Korean medicine consisting basically of 14 herbs (Lee et al 2010(Lee et al , 2012. Pharmacological studies of ST have been confined to its roles in gastroprotection (Kim and Lee 1988) and immune regulation (Lee and Kim 1998).…”
Section: Introductionmentioning
confidence: 99%